Group for family/caregivers of elderly with Alzheimer’s: experience of teachers based on the complexity - Silomar Ilha; Dirce Stein Backes; Silvana Sidney Costa Santos; Daiane Porto Gautério-Abreu; Claudia Zamberlan; Tereza Cristina Blasi (Rev Rene)
Objective: to understand the relationships experienced by a group of health care teachers directed to family members/caregivers of older people with Alzheimer’s disease. Methods: qualitative research, conducted with five teachers participating in a support group developed in a university. Data collected by the technique of focus group submitted to Focal Strategic Analysis. Results: six categories were identified: Difficulty in raising awareness of the participants about Alzheimer’s disease; The interdisciplinary in the guidelines; Exchange of knowledge; Acquire/search for more knowledge; Expansion/socialization of knowledge about Alzheimer’s disease: an even existing challenge; Absence attendance: a threat to the existence of the group. Conclusion: the disorder is a reality experienced by teachers in the group, which is (re)organize constantly seeking the best way to guide and foster care.